Catalytical feature of optical nanoprobes of boron nitride quantum dots in the presence of Cu2+ for the determination of dopamine. Issue 18 (12th August 2021) - Fan, Xiushuang; Qiu, Jinpeng; Peng, Chao; Ren, Jiangtao; Xing, Huanhuan; Bi, Chuyao; Yin, Jianyuan; Li, Jing
Abstract : Boron nitride quantum dots (BNQDs) can catalyze polymerization of dopamine and formation of polydopamine in the co-existence of Cu 2+, resulting in fluorescence quenching of BNQDs, which provides the new strategy for dopamine analysis. Abstract : Monitoring the concentration of dopamine (DA) is vital for preventing and diagnosing DA related diseases. In contrast to the traditional sensing methods for DA, in which direct or indirect effects on the optical probes are often recorded, a novel sensing concept is disclosed based on as a result of the in situ formation of polydopamine (PDA) originating from the synergetic effect between boron nitride quantum dots (BNQDs) and Cu 2+ . In the co-presence of BNQDs and Cu 2+, DA was catalytically oxidized to PDA, accompanied by an obvious color change from colorless to brown. In contrast to previous reports, in which BNQDs have been employed as an optical probe, herein, the BNQDs not only acted as the optical energy donor, but also as the catalysts for the formation of PDA. The quenching efficiency resulting from the inner filter effect and the electron transfer between the BNQDs and PDA was directly proportional to the concentration of DA, ranging linearly from 2 to 80 μM with a limit of detection of 0.49 μM. The present system exhibited an outstanding selectivity for DA among other interfering coexisting biomolecules. Furthermore, the practical application of the proposed platform was verified by assaying DA in human plasma samples, and satisfactory recoveries ranging from 101.24% to 111.98% were obtained. With the satisfactory reliability, repeatability and stability, the proposed simple sensor showed significant potential for use in DA detection in other biomedical applications.